EFFECT OF PER, DER, EPS, AND PBV ON STOCK PRICES IN BANKING COMPANIES ON IDX - Abram Elieser; Deasy Arisandy Aruan; Bintori Dongoran; Mariabeth Simanjuntak (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2022)
This research intends to analyze the influence of PER, DER, EPS and PBV on share prices partially and simultaneously in banking companies listed on the IDX for the period 2016- 2019. This finding uses a population of 42 banking companies registered with the IDX for the period 2016 - 2019. This research uses quantitative methods. The secondary datai usedi is obtained from the official website of the www.idx.co.id and www.idnfinancials.com. In this study used for sampling is the Purposive Sampling technique. The method of investigation used is a double linear regression method. The findings showed that PER, DER and EPS partially had a negative and significant effect oni the stocki price, pbv partially had a positive and significant effect on the stock price. Based on simultaneous PER, DER, EPS and PBV significantly affect the stock price in banking companies listed on the Indonesia Stock Exchange (IDX) period 2016-2019